Accessibility for Persons with Disabilities in Trans Metro Bandung Services - Jeremia Gom Gom Parulian Simanjuntak (The Center for Disability Studies and Services Brawijaya University, 2019)
Public services, especially public transportation services for persons with disabilities, have not been well organized and have not been based on equality even though various laws and regulations have regulated them. One form of implementing equality for persons with disabilities is the provision of accessibility facilities to support and assist them in using a service. Based on the characteristics of the research object, the method used is a qualitative method with a descriptive approach. The technique of collecting data is done by in-depth interviews, observations, and library studies. This article is intended to provide an overview regarding the provision of accessibility facilities for persons with disabilities in the Trans Metro Bandung services and also provides an overview regarding the implementation of Trans Metro Bandung services for persons with disabilities in the city of Bandung.